Effectiveness of Traffic Law Enforcement and Alternative Models for Solving It at the Central Tapanuli Police - Wahono, Totok Catur; Isnaini, Isnaini; Frensh, Wenggedes (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
Traffic law enforcement is one of the important efforts in creating order and driving safety. This study aims to analyze the effectiveness of law enforcement against traffic violations in the Central Tapanuli Police Station, identify the factors that cause the high number of violations, and propose a more effective alternative solution model. This study uses a qualitative method with a descriptive approach. Data was obtained through interviews with police officers and the public, observations at several traffic points, and documentation studies related to traffic policies and regulations. The results of the study show that law enforcement at the Central Tapanuli Police still faces various obstacles, including low public awareness of the law, lack of supervision, limited infrastructure, and poor driving culture. Law enforcement, which currently focuses more on repressive measures, has not been able to create a significant deterrent effect. Therefore, more effective alternative models are needed, such as the SIM Point System, Traffic Education for Offenders, Social Sanctions, and ETLE Strengthening. This model is expected to increase public awareness and reduce the number of traffic violations in a more sustainable manner. With the implementation of a more innovative and education-based strategy, it is hoped that the level of traffic compliance in Central Tapanuli can increase significantly. The conclusion of this study indicates that a combination of strict law enforcement and a preventive approach is the main key in creating a more orderly and safe traffic system.